2011
DOI: 10.1104/pp.111.188474
|View full text |Cite
|
Sign up to set email alerts
|

Nucleoid-Enriched Proteomes in Developing Plastids and Chloroplasts from Maize Leaves: A New Conceptual Framework for Nucleoid Functions      

Abstract: Plastids contain multiple copies of the plastid chromosome, folded together with proteins and RNA into nucleoids. The degree to which components of the plastid gene expression and protein biogenesis machineries are nucleoid associated, and the factors involved in plastid DNA organization, repair, and replication, are poorly understood. To provide a conceptual framework for nucleoid function, we characterized the proteomes of highly enriched nucleoid fractions of proplastids and mature chloroplasts isolated fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
247
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 226 publications
(267 citation statements)
references
References 164 publications
(196 reference statements)
19
247
0
1
Order By: Relevance
“…The strong visible phenotype of w2 mutants contrasts with those findings, and shows that w2 function is essential for chloroplast biogenesis. This is consistent with proteome studies, which have detected W2 but not its paralog in various chloroplast subfractions (Majeran et al, 2012).…”
Section: Maize Locus W2 (Grmzm2g480171) Encodes a Chloroplast Dna Polsupporting
confidence: 92%
See 1 more Smart Citation
“…The strong visible phenotype of w2 mutants contrasts with those findings, and shows that w2 function is essential for chloroplast biogenesis. This is consistent with proteome studies, which have detected W2 but not its paralog in various chloroplast subfractions (Majeran et al, 2012).…”
Section: Maize Locus W2 (Grmzm2g480171) Encodes a Chloroplast Dna Polsupporting
confidence: 92%
“…The division of labor between organelle DNA polymerases differs in Arabidopsis, where a pair of paralogs function redundantly to support DNA replication in both organelles (Parent et al, 2011). W2 has been detected in proteome analyses of purified chloroplasts (Majeran et al, 2012), but the W2 paralog has not been detected in either chloroplasts or mitochondria. Our results are consistent with the possibility that W2 is the only source of DNA polymerase in chloroplasts, as the residual chloroplast DNA signal in the most severely affected samples (approximately 1% of normal in the apical section of w2-mum2 leaves) might arise from small revertant sectors.…”
Section: Discussionmentioning
confidence: 99%
“…The TAC fraction is prepared from plastid membranes by release of the nucleoids with detergents and by subsequent purification involving sepharose gel filtration and other steps (Krause and Krupinska 2000;Pfalz et al 2006). Recent proteomic analyses of these (Pfalz et al 2006;Melonek et al 2012) and other nucleoid-enriched fractions (Phinney and Thelen 2005;Majeran et al 2012) have revealed that several of the newly identified DNA binding proteins were not inherited from the prokaryotic ancestors. Plastid proteins homologous to the abundant prokaryotic HU protein, on the other hand, were not detected in higher plants which stands in contrast to their identification in some algal plastids (Karcher et al 2009), in the apicoplasts of apicomplexans (Sato et al 2003) as well as in some dinoflagellates (Chan et al 2006).…”
Section: Analysis Of the Protein Composition Of Plastid Nucleoidsmentioning
confidence: 99%
“…Accordingly, core subunits of the plastid-encoded RNA polymerase, PEP, have been identified in most of the proteomic studies of plastid nucleoid fractions of dicots (i.e. Arabidopsis, mustard, spinach, pea) (Phinney and Thelen 2005;Pfalz et al 2006;Melonek et al 2012) as well as monocots (i.e., maize) (Majeran et al 2012). A preparation, where only the core PEP and very tightly associated subunits were preserved, contained an additional ten proteins that were termed PEP-associated proteins (for PAPs) (Steiner et al 2011).…”
Section: Transcriptionmentioning
confidence: 99%
See 1 more Smart Citation